Improving the Abilities of Science Learning Outcomes About Heat Transfer in Class V Students of SD IT Uswatun Hasanah Through the Singing Method - Astri, Aas; Suwanto, Suwanto; Leini Saragih, Srimis (Pusdikra Publishing, 2024)
This research aims to describe efforts to improve students' ability to understand heat transfer in fifth grade science lessons at SD IT Uswatun Hasanah, Banjar City. To achieve this goal, Classroom Action Research will be carried out on 21 students using the singing method. There are 2 cycles in this research. Each cycle goes through four stages, consisting of (1) planning, (2) implementing learning improvements, (3) data collection, and (4) reflection. Data were collected using a learning outcomes test in the form of a questionnaire with a total of 10 questions. Based on the research stages, the results showed that in cycle 1 only 43% had completed the KKM score of 75. And this increased to 100% in cycle 2. Therefore, the use of the singing method had a positive impact in improving student learning outcomes in the heat transfer science subject. The material presented becomes easier for students to accept and students feel happy so that students are actively involved and also motivated in class so that learning objectives are achieved well.